Responsible leadership - Maak, Thomas; Pless, Nicolas (Routledge, 2006)
Aims to answer the challenge of defining responsible leadership in an era of globalization. This book is arranged in three main parts: What is responsible leadership? What makes a responsible leader? How to develop responsible leadership in business? It is useful to business students, academics, and professionals.